Validation of 205 MHz wind profiler radar located at Cochin, India, using radiosonde wind measurements. Issue 3 (3rd March 2016) - Kottayil, Ajil; Mohanakumar, K.; Samson, Titu; Rebello, Rejoy; Manoj, M. G.; Varadarajan, Rakesh; Santosh, K. R.; Mohanan, P.; Vasudevan, K.
Abstract: A novel Mini Wind Profiling radar at 205 MHz has been set up at Cochin (10.04°N, 76.33°E), India, with the main objective of studying the dynamics of the Indian summer monsoon. This paper presents the first time validation of this Mini Wind Profiler using collocated radiosonde wind measurements. The wind profiles within 1–6 km altitude range have been validated. The radar wind profiles match very well with the radiosondes both in terms of magnitude and direction and ideally captures the day‐to‐day wind variations. The correlation between radar and radiosonde's zonal and meridional wind is 0.91 and 0.85, respectively. The standard deviation of the difference between radiosonde and radar for zonal wind is found to be 1.95 m s −1 and 1.56 m s −1 for meridional wind. These observations are seen to agree quite well with other established wind profiler radars operating elsewhere in the world. The results show that the 205 MHz Wind Profiler is capable of providing high‐quality wind data, and this could be pivotal for monsoon studies in years to come. Key Points: The 205 MHz wind profiler has been set up for the first time in the world A first validation of 205 MHz wind profiler First wind profiler in the near‐equatorial region